This Marx is a Game Changer: Rethinking the Economics of Sport. Issue 1 (3rd April 2021) - Potts, Nick
Abstract : Potts argues that Marx's economics provides a far more useful basis to analysing the business of sport than conventional mainstream economics. From understanding business as a dual process of providing use-values and making money, through what elite sport-peoples' wages actually are, to understanding how business competition works dynamically, Marx's theory provides a superior representation of reality, allowing past trends to be explained and future developments to be more reliably predicted. Furthermore, the Marxist concept of distinct phases of the Social Structure of Accumulation provides an excellent approach to analysing central developments in sports, like the set-up of the English Premier League.